Enhancing Climate Change Mitigation through Agriculture. (OECD Publishing, 2019)
Agriculture, with its growing contribution to global greenhouse gas emissions and opportunities to mitigate emissions, can help close the gap between existing global mitigation efforts and those that are needed to keep global warming to between 1.5 °C and 2 °C by the end of the century. Global scale and farm scale analyses are used to evaluate both the effectiveness of different policy options to reduce agricultural emissions, and the impact on competitiveness, farm income, food security, and government finances. In order to contribute to global mitigation efforts, countries will need to design agricultural policy measures that can navigate these trade-offs within the context of their national policy priorities and objectives. As most countries have not yet implemented policies to reduce emissions from agriculture, the analyses provided here come at an opportune time to inform this policy development.